P228 Impact of long-acting bronchodilator therapy on mortality in copd: a real-life retrospective cohort study. (14th November 2013) - Manoharan, A; Short, PM; Anderson, WJ; Lipworth, BJ
Abstract : Introduction and Objectives: Long-acting muscarinic antagonists (LAMA) and long-acting beta-agonists (LABA) are first-line treatments for COPD. The addition of inhaled corticosteroids (ICS) is recommended for patients with frequent exacerbations who are not adequately controlled with long-acting bronchodilators. These medications have been largely evaluated independently in placebo controlled randomised trials. In this 'real-life' study we investigated the impact of these medications used independently and in combination on mortality. Methods: We conducted a retrospective cohort study using data from patients with a diagnosis of COPD in NHS Tayside between 2001 and 2010. All-cause and cardiovascular mortality was assessed using Cox proportional hazard regression after adjustment for FEV1, age, sex, smoking pack-years, oxygen saturation, cardiovascular and respiratory admissions; cardiovascular medications and diabetes. Patients on short-acting bronchodilators only were used as the controls. Results: A total of 5048 patients were included in the study with mean age at diagnosis of 69.4 years and mean follow-up of 4.0 years. 623 were on long-acting bronchodilators only, 3510 on long-acting bronchodilator and ICS; and 915 controls. Crude hazard ratios are shown in Table 1 . Adjusted HR (95%CI) for all-cause mortality for LABA only, LAMA only; and LABA + LAMA were 0.70 (0.45–1.09), 0.52 (0.37–0.73) and 0.53 (0.34–0.84) respectively. Adjusted HR for all-cause mortality for LABA + ICS, LAMA + ICS; LABA + LAMA + ICS were 0.56 (0.45 – 0.70), 0.34 (0.25 – 0.47) and 0.29 (0.24 – 0.36) respectively. Adjusted HR for cardiovascular mortality for LABA only, LAMA only; and LABA + LAMA were 0.63 (0.28–1.44), 0.41 (0.21 – 0.79) and 0.39 (0.17 – 0.90) respectively, and for LABA + ICS, LAMA + ICS; LABA + LAMA + ICS were 0.50 (0.33 – 0.75), 0.23 (0.12 – 0.45) and 0.22 (0.15 – 0.33) respectively. Conclusions: LABA monotherapy does not confer any mortality benefit but when used in combination with ICS reduces both all-cause and cardiovascular mortality. In contrast, LAMA whether given alone or in combination with a LABA and /or ICS reduces both all-cause and cardiovascular mortality. This 'real-life' study suggests that LABA should perhaps not be given as monotherapy but only in conjunction with a LAMA or ICS.